A characterization study for the properties of dust particles collected on photovoltaic (PV) panels in Sharjah, United Arab Emirates. (June 2021) - Dhaouadi, Rached; Al-Othman, Amani; Aidan, Ahmed A.; Tawalbeh, Muhammad; Zannerni, Rawan
Abstract: Dust accumulation on photovoltaic (PV) modules is responsible for the reduction in solar radiation received and/or transmitted, hence, decreases the efficiency of the PV cells. To enhance the performance of PV modules, the nature and the structure of dust should be evaluated. This paper investigates the seasonal variability of dust and PV soiling losses over 4 months (15 weeks, over the summer of 2018) in a soiling station deployed at the American University of Sharjah, UAE. A custom-made setup was employed to collect the dust samples on glass sheets. This will provide a better understanding of the soil deposition rates and composition. The accumulated dust was characterized for its morphological and elemental properties. The dust samples were directly collected from the panels mounted outdoor in the desert environment. Various characterization techniques were performed to determine the dust samples' composition. The results showed that the dust particles are mostly rich in carbon, oxygen, calcium, silicon, thus indicating the presence of silica and calcite. UV–Vis results showed a decrease in transmittance of 30% after 15 weeks of soiling. This results of this work are essential for the development of proper self-cleaning techniques for PV modules deployed in Sharjah. Highlights: The dust accumulation rate of 0.7 mg/week was recorded at 25°. A decrease in transmittance of about 30% after 15 weeks of soiling was reported. High oxygen and carbon content were reported in the dust samples. The results reported here provide a basis to develop a proper cleaning technique.